Consumer Conformity and Continuance Intention: A Study Case Approach of Facebook and WhatsApp - Princes, Elfindah; So, Idris Gautama; Abdinagoro, Sri Bramantoro; Manurung, Adler Haymans (APPS Publications, 2025)
ABSTRACT Purpose - This study aims to explore the phenomenon of consumer conformity and its impact on the continuance and reuse intention of digital communication platforms, particularly in the context of policy changes that force users into making critical decisions. Using the recent case of WhatsApp and Facebook's policy updates as a backdrop, this study examines how consumer conformity influences user behavior and intentions to continue or abandon a service. Methodology - The research is conceptual in nature, employing an integrative approach based on the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM). A comparative analysis is conducted through two proposed scenarios to understand user decisions following sudden policy changes, emphasizing the psychological factors of conformity, perceived value, trust, and perceived risk. Findings - The findings suggest that when consumers are faced with limited choices, such as accepting unfavorable terms or discontinuing service, informational and normative conformity significantly influence continuance intention. Factors such as perceived security, service quality, satisfaction, and perceived usefulness are found to moderate the relationship between conformity and continuance intention. Additionally, previous experience, trust, and self-efficacy emerge as strong determinants of users' willingness to reuse or abandon the service after policy disruptions. Novelty - Unlike previous studies that treat continuance intention purely as a result of satisfaction and usefulness, this study introduces the element of forced conformity and policy-driven decision-making into the behavioral model. It proposes a dynamic framework that incorporates psychological contract violation, trust restoration strategies, and conformity types (informational and normative) in explaining consumer behavior in digital platforms.